Apports de l’étude archéo-ichtyologique de l’Isle-Saint-Georges (Gironde) au commerce de poissons marins sur l’axe aquitain : processus interculturel et modalités de diffusion (ier s. av. J.-C. – iiie s. apr. J.-C.) - Brice Ephrem (Gallia)
Fresh fish consumption in the Roman World is commonly accepted as a marker of social status. However, the modes of inland trade have never been addressed for the Aquitaine region. We propose to study this question in order to measure the impact of Roman influence and interaction processes in the consumption and trade of fresh sea fish. The contribution of original archaeo-ichthyological data from the L’Isle-Saint-Georges site (Gironde) provides information about the advent and definition of markers of consumption under Roman influence. The trade of these fish by terrestrial and fluvial routes in Aquitaine contributed to the diffusion of Mediterranean-inspired food patterns, reflecting socio-economic adaptation to the Atlantic environment.